Psychological factors increase the risk of ovarian cancer - Shuo Geng; Xu Zhang; Xiaoyu Zhu; Yadi Wang; Yingchen Wang; Yewu Sun (Taylor & Francis Group, 2023)
This study evaluated whether psychological stress increases the incidence of ovarian cancer. A literature search of the electronic databases PubMed and Web of Science from the date of inception to August 2022 was undertaken. Studies with data on psychosocial factors associated with ovarian cancer incidence were included in this study. A random-effect model meta-analysis was undertaken to estimate these data. We used subgroup analysis to adjust for heterogeneity. A total of 4 articles, 10 sets of data, 8 cohort studies, and 2 case-control studies from 682 records were included in this review. Meta-analyses of the included cohort study subgroups suggested that psychological factors increase the risk of ovarian cancer (effect size = 1.37, 95% CI: 1.20-1.53); the subgroup of case-control studies suggested that psychological factors did not increase ovarian cancer risk (effect size = 0.84, 95% CI: 0.70-0.98). These findings indicate that psychological stress is a possible new risk factor for ovarian cancer. Prospero registration number: CRD42022357983IMPACT STATEMENT What is already known on this subject? Psychological stress has been shown to increase the risk of many diseases. The relationship between psychological stress and the incidence of ovarian cancer has not been confirmed. What do the results of this study add? The effect of psychological stress on the risk of ovarian cancer was estimated using meta-analysis as an overall ratio. What are the implications of these findings for clinical practice and/or further research? Relaxing psychological stress and appropriate psychotherapy in clinical settings can help reduce the risk of ovarian cancer.